Education Policy 2025: Between Hope, Reality and Implementation - Nur Ismianah; Mz, Muhammad Amanulloh (RAM PUBLISHER, 2025)
The year 2025 is an important milestone in the journey of education reform in Indonesia. The government through the Ministry of Education, Culture, Research, and Technology has launched various strategic policies, such as strengthening the Merdeka curriculum, expanding access to 13-year education, and transforming the national evaluation system through SPMB. This article critically examines the dynamics between the ideal expectations brought by these policies, the realities on the ground faced by teachers, students, and educational institutions, and the implementation challenges that arise in various regions. With a policy analysis approach and case studies, this paper aims to provide a comprehensive overview of the effectiveness of education policies in 2025 as well as recommendations for continuous improvement towards a more inclusive, equitable, and adaptive education system to the changing times.